Adverse effects of propranolol in a fulminant ulcerated infantile hemangioma - Aida Oulehri; Hanane Baybay; Sara Elloudi; Zakia Douhi; Fatima Zahra Mernissi (Our Dermatology Online, 2022)
Infantile hemangiomas (IHs) are the most common tumors of infancy, with a global prevalence estimated at 1% to 10% of infants. Most hemangiomas are small and regress spontaneously without a need for intervention. However, 5% to 10 % of hemangiomas may cause serious complications and require treatment. Herein, we report the case of a two-month-old female infant with a left hemifacial hemangioma, which became severely ulcerated after the introduction of propranolol. We also report a good improvement afterwards due to combined therapy. An ulcerated infantile hemangioma is the most common complication seen in an IH, which may present a therapeutic challenge especially in the case of concurrent hemorrhage or infection. Although numerous studies support its efficacy and reduced side effects. propranolol may worsen the ulceration of an IH, possibly reflecting a reduced blood flow, causing peripheral ischemia. In some cases of IH with complex ulceration, monotherapy with propranolol may be insufficient.